1986
DOI: 10.1002/eji.1830160815
|View full text |Cite
|
Sign up to set email alerts
|

Immunoglobulin heavy chain gene rearrangements in X‐linked agammaglobulinemia

Abstract: Physicians and Surgeons, New YorkX-linked agammaglobulinemia (XLA) appears to involve a defect in human B lymphocyte differentiation which is manifested at the pre-B cell stage. The defect segregates as an X-linked recessive trait but is not a single genetic entity. IgM-producing B cell clones were established by Epstein-Barr virus transformation of peripheral blood mononuclear cells of patients with the XLA defect linked to the DXS3 and DXS17 chromosomal loci. Individual XLA B cell clones were demonstrated to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
1

Year Published

1986
1986
2000
2000

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 48 publications
(14 citation statements)
references
References 32 publications
0
13
1
Order By: Relevance
“…These results are in agreement with previous phenotypic characterization ofthe bone marrow cell population in XLA patients (62,63). By contrast to other reports (3,9,49,64), our data indicate that rearrangement mechanisms seem fully functional, although a possible decrease in efficiency ofthe pro-B to pre-B transition, as followed by the DJ to VDJ rearrangement cannot be quantitatively as- Our analysis performed on XLA bone marrow cells provides direct access to the pre-B cell repertoire which is truly representative of the defect. Analysis of EBV clones derived from XLA patients may therefore contain a bias linked to the selection ofa minor population of B cells that have escaped the XLA defect (1 1, 12).…”
Section: Methodscontrasting
confidence: 96%
See 2 more Smart Citations
“…These results are in agreement with previous phenotypic characterization ofthe bone marrow cell population in XLA patients (62,63). By contrast to other reports (3,9,49,64), our data indicate that rearrangement mechanisms seem fully functional, although a possible decrease in efficiency ofthe pro-B to pre-B transition, as followed by the DJ to VDJ rearrangement cannot be quantitatively as- Our analysis performed on XLA bone marrow cells provides direct access to the pre-B cell repertoire which is truly representative of the defect. Analysis of EBV clones derived from XLA patients may therefore contain a bias linked to the selection ofa minor population of B cells that have escaped the XLA defect (1 1, 12).…”
Section: Methodscontrasting
confidence: 96%
“…Analysis of the X chromosome inactivation in XLA carrier women has shown that the defect was specific to the B cell lineage (3)(4)(5)(6)(7). The exact nature of the defect is, however, not known.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In X-linked agammaglobulinemia some sequences of the junctions in VDJ rearrangements have been reported [15][16][17]. In this patient, the sequences examined in the junctions of VDJ rearrangements were in frame, and N insertion was also detected.…”
Section: Discussionmentioning
confidence: 76%
“…Epstein-Barr virus-transformed B-cell lines from patients with XLA have been shown to secrete IgM constitutively or in response to B-cell growth and differentiation factors [10], indicating that failure of B-cell differentiation is not absolute. Furthermore, EBV-transformed B-cell lines from XLA patients were able to form complete VnDJH rearrangements [11]. An adequate yield of Bcells was obtained from patient 1, and these gave very low IgG and IgA PFC, and slightly low IgM PFC, when co-cultured with (C) Tn and PWM.…”
Section: Resultsmentioning
confidence: 99%